Pengembangan Ular Tangga IPA sebagai Media Pembelajaran pada Materi Pemanasan Global untuk Peserta Didik Kelas VII SMP/MTs - Irma humairoturrosyidah, Irma (Discovery, 2024)
This research aims to develop Snakes and Ladders Science as a learning medium for Global Warming material for class VII students at MTs Negeri 11 Jombang. This research includes development research using the ADDIE model through the stages of analysis, design, development and evaluation. The result of the development is Snakes and Ladders Science as a learning medium with an average validity value of 85.74% by material experts, 89.28% by media experts, and 94.64% by science teachers at MTs Negeri 11 Jombang. From the three validators, an average validity value of 89.89% was obtained with very valid criteria. This research was motivated by a lack of student interest and interest in learning because the learning methods used by teachers were less innovative and teachers had not utilized appropriate media to make it easier for students to understand the material presented, especially on Global Warming. Students prefer learning while playing. For this reason, it is necessary to develop innovative learning media. The data collection technique in this development research was through a questionnaire distributed to 33 students at MTs Negeri 11 Jombang on February 10 2021. The data obtained from the questionnaire was analyzed descriptively qualitatively and quantitatively.